Perioperative Ultrasound Training in Anesthesiology: A Call to Action. (June 2016) - Mahmood, Feroze; Matyal, Robina; Skubas, Nikolaos; Montealegre-Gallegos, Mario; Swaminathan, Madhav; Denault, Andre; Sniecinski, Roman; Mitchell, John D.; Taylor, Mark; Haskins, Stephen; Shahul, Sajid; Oren-Grinberg, Achikam; et al.
Abstract : Supplemental Digital Content is available in the text.